111k views
4 votes
let f(x)=log(x^2-2x) and g(x)=x/x-1. which expression represents (fog)(x)? a)log(x^3-2x^2/x-1) b)xlog(x^2-2x)/x-1 c)log(x^2-2x)/log(x^2-2x)-1 d)log(x^2-2x(x-1/(x-1)^2)

User Tanzin
by
4.7k points

1 Answer

4 votes

Problem: let f(x)=log(x^2-2x) and g(x)=x/x-1. which expression represents (fog)(x)?

Solution:

notice that:


(f\circ g)(x)\text{ = f(g(x))}

then, the composition would be:


(f\circ g)(x)\text{ = f(g(x)) = log( (}(x)/(x-1))^2-2\text{(}(x)/(x-1))\text{ )}

this is equivalent to


=\text{ log( }(x^2)/((x-1)^2)^{}-(2x)/(x-1)\text{)}

this is equivalent to (Making common factor):


=\text{ log( }(x^2-2x(x-1))/((x-1)^2))

then the correct answer would be:


=\text{ log( }(x^2-2x(x-1))/((x-1)^2))

User Serbitar
by
5.8k points